DETERMINANTS OF LIBRARY USE AMONGST UNIVERSITY STUDENTS - Zei, Mei Teoh; Tan, Andrew K.G. (Malaysian Journal of Library and Information Science, 2011)
The purpose of the study is to examine the factors affecting library use amongst university students. Logistic regression analysis is applied on data collected using stratified random questionnaire-based interviews of 388 students of a public university in Malaysia. Results of the marginal effects indicate that students of Indian and other descent are more likely to use the library than their Malay cohorts. In addition, those who have attended library induction sessions, those who believe that the library provides a useful avenue for them to achieve their academic goals, and frequent online users are more likely to utilize the library than their cohorts, all else equal. Students in their third/fourth/final year of studies have a lower propensity for library visits than their second year counterparts, ceteris paribus. Meanwhile, factors such as gender, parental education, campus residence, field of study, and job status do not affect library utilization in a statistically significant manner. Based on theseresults, several observations are noted vis-Ã -vis the determinants of library use amongst university students